2021
DOI: 10.1142/s0219877021500103
|View full text |Cite
|
Sign up to set email alerts
|

How to Organize Digital Innovation? The Role of Involvement, Structure, and Technology

Abstract: Innovation, especially digital innovation, is indispensable for organizations that want to remain competitive. Employees play a crucial role in developing innovations, but the use of digital technologies for innovation methods that foster employee-driven innovation has rarely been researched. Using a sample of 215 participants and two innovation methods (i.e. digital, non-digital), we show that employees value a digital innovation more if they are involved in the digital innovation, the involvement follows a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It has also produced several changes in the approach to business relations as an effect of the accelerated digital transformation processes driven by the pandemic crisis [78]. At the same time, it has been shown that employees adopt digital innovations faster if they are directly involved in this process [79]. There is a significant connection between digital organizational culture and digital capabilities with digital innovation, and organizational training can be a mediator between digital capabilities, digital organizational culture, and digital innovation [80].…”
Section: Digital Accelerationmentioning
confidence: 99%
“…It has also produced several changes in the approach to business relations as an effect of the accelerated digital transformation processes driven by the pandemic crisis [78]. At the same time, it has been shown that employees adopt digital innovations faster if they are directly involved in this process [79]. There is a significant connection between digital organizational culture and digital capabilities with digital innovation, and organizational training can be a mediator between digital capabilities, digital organizational culture, and digital innovation [80].…”
Section: Digital Accelerationmentioning
confidence: 99%